Trade Credit and Relationships - Felipe Benguria; Alvaro Garcia-Marin; Tim Schmidt-Eisenlohr (Center for Economic Studies and ifo Institute (CESifo), 2023)
Most domestic and international firm-to-firm transactions rely on trade credit, where sellers grant buyers time to pay the invoice after delivery. Exploiting Chilean and Colombian transaction-level trade data, this paper documents new facts about trade credit use: trade credit use increases with firm-to-firm relationship length, an effect that is stronger for destination (source) countries with weaker (stronger) contract enforcement and for trade in differentiated goods. The paper develops a model featuring enforcement frictions, learning, and a financing cost advantage of trade credit that can rationalize these patterns. Initially, as there is uncertainty about the reliability of the trading partner, payment risk is a key factor limiting the use of trade credit. Through learning, this uncertainty resolves within a relationship over time. For older relationships, the payment choice is, therefore, only determined by the financing cost advantage of trade credit, and all relationships rely on trade credit in the long run. The paper thereby suggests a new benefit of long-term trade relationships: the ability to save on financing costs through the use of trade credit.
Keywords: F12; F14; G21; G32; 330; trade credit; relationships; learning; financing costs; risk